(untitled) (Global Journal of Medical Research, 2020)
Merkel Cell Carcinoma (MCC) is extremely rare and aggressive, with an overall survival of 40% in 5 years. The non-oncological physician has large difficulty about the correct approach of this pathology. We report the sixth case of MCC in a young healthy patient (woman, 19 years old) described in the medical literature, who was treated twice for sebaceous cyst, evolved with local disease progression, needed a larger resection and, after adjuvant therapy, remains no tumor recurrence. Despite being an extremely rare neoplasm, therapeutics should not be underestimated by non-oncological physician because this cancer is too aggressive, and the correct oncological approach could result in increased progression-free survival for these patients.